Waist circumference, waist‐to‐height ratio and BMI percentiles in children aged 5 to 19 years in India: A population‐based study - Avina Sarna; Akash Porwal; Rajib Acharya; Sana Ashraf; Sowmya Ramesh; Nizamuddin Khan; Sikha Sinha; Harshpal Singh Sachdev (Wiley, 2021)
Abstract Objective Nationally representative percentiles for waist circumference (WC), waist‐to‐height‐ratio (WHtR), and body mass index (BMI) are not available for children and adolescents in India. Methods Using LMS method, age‐ and gender‐specific reference growth charts were constructed for WC (n = 68,261), WHtR (n = 68,261), and BMI (n = 67,741) from children/adolescents aged 5-19 years who participated in a nationally representative survey. General obesity, indicating overall obesity, was defined as age-sex‐specific BMI z‐scores ≥ 95th percentile. Central obesity was defined in three ways: WC ≥ 90th percentile, WHtR ≥ 0.5, and both WC ≥ 90th percentile and WHtR ≥ 0.5. Findings WC and BMI percentiles for boys and girls are lower than those previously reported from India and several other countries. The BMI percentiles are lower than the WHO 2007 reference population. The prevalence of general obesity using India specific BMI centiles was 2.9% (95% CI: 2.6-3.2). The prevalence of central obesity was 6.1% (95% CI: 5.7-6.6) using WC ≥ 90th percentile, 5.3% (95% CI: 5.0-5.7) using WHtR ≥ 0.5, and 3.6% using both criteria. Three‐fourth of children with general obesity also had central obesity based on WC ≥ 90th. Conclusions Indian children are thinner than Caucasian and other Asian children, and the global WHO reference population. Using India specific reference, the prevalence of central obesity is higher than general obesity with a significant overlap between the two.